Methylation of the CpG sites in the myotonic dystrophy locus does not correlate with CTG expansion size or with the congenital form of the disease. Issue 10 (19th July 2010) - Spits, C; Seneca, S; Hilven, P; Liebaers, I; Sermon, K
Abstract : We have studied the methylation status of the sequence 152 nucleotides upstream of the CTG repeat of the DM1 locus in patients' peripheral blood. We used the methylation-sensitive endonucleases SacII, HpaII and HhaI, followed by PCR. This allowed to correlate the methylation status of each CTG allele with its size. Contrary to previous findings, only the SacII site is often but not always differentially methylated among expanded CTG alleles. Importantly, this methylation was not restricted to congenital DM1, nor to large expansions, as it was also present in DM1 patients with a classical phenotype and various expansion sizes. On the other hand, we did not find any methylated alleles on the HhaI and HpaII sites, as was reported by Steinbach et al, which is in line with the results of Shaw and collaborators. The size range of the repeat expansions with methylation was from as small as 300 to as large as 2800 repeats.